The impacts of work-life balance and self-efficacy on job satisfaction among fast food industry workers in Ipoh, Perak - Ching, Loo Pei; Low, Wan Chee (2019)
This study is investigated the impacts between work-life balance and self-efficacy on job satisfaction among fast food industry workers at Ipoh. Most of the proposed studies do not evaluate the variables clearly and simultaneously. It is crucial to focus on because it can highlight the importance of job satisfaction by linking and promoting the work-life balance and self-efficacy among fast food industry employees. This study attempts to test the linkage among these variables that work-life balance and self-efficacy influence job satisfaction. 300 of fast-food industry employees have been selected by purposive sampling method and completed the tests on work-life balance, self-efficacy and job satisfaction. A self-administered questionnaire which consisted Work Life Balance Scale, Occupational Self-Efficacy Scale and Generic Job Satisfaction Scale was employed. Pearson Correlation revealed that self-efficacy and work-life balance are significantly correlated with job satisfaction. Furthermore, results of multiple regression revealed that self-efficacy is the strongest predictor for job satisfaction, followed by work-life balance. There is no significant difference between male and female employees in terms of work-life balance, self-efficacy and job satisfaction. This study delivers valuable insight for human resource practitioners and policy makers who are concerned with the factors that contribute to job satisfaction among fast food industry employees.